Optical properties of hybrid quasiperiodic Fibonacci photonic crystals. Issue 2 (March 2020) - Zhong, Yibing; Shi, Shengli; Gao, Mingxing; Wang, Yuhao; Lv, Chunyan; Dong, Daxing
Abstract: In this paper, we exploit new optical properties of hybrid quasiperiodic Fibonacci photonic crystals by the transfer matrix method. The quasiperiodic photonic crystals are consist of various generation orders of photonic crystal series that follow the Fibonacci sequence. By regarding the building blocks like S 3, S 4, S 5 as a unit cell ( S 3 S 4 S 5 ) of photonic crystals, we get multiple bandgaps in its spectrum. Furthermore, the bandgaps of the Fibonacci hybrid photonic crystals are tunable by merely altering the refractive index of the dielectric materials. The proposed configuration is a promising candidate as a multichannel filter and a refractive index sensor in the field of integrated photonic circuits.